Tipologi Tafsir Al-Qur'an di Madura: Tafsir Tradisionalis, Modernis, dan Tradisionalis-Progresif - Ramdhani, Fawaidur (Lajnah Pentashihan Mushaf Al-Qur'an, 2023)
This article maps the typology of the Qur’anic interpretation in Madura based on tendencies in socio-religious thought. This study is part of a library research on the Qur’anic interpretation in Madura. The first typology is modernist interpretation, represented by Tapser Sorat Yaa-siin by Muhammad Irsyad, seen through its emphasis on returning to the Qur’an and Hadith, rejection of myths, mysticism, blind imitation, and opposition to visiting the graves of saints. The second typology is traditionalist interpretation represented by Tafsir Firdaus an-Na'im by Thaifur Ali Wafa. The indicators include reliance on riwayah (narrations), strict limitations on personal opinions (al-ra’y), a strong adherence to the traditions of the school of thought (mazhab), and acceptance, even advocacy, of practices like seeking intercession (tawasul) and visiting the grave of saints. The last typology is the traditionalist-progressive interpretation, represented by Tafsir Alqur’anul Karim Nurul Huda by Mudhar Tamim. Indications of traditionalist-progressive thinking in this interpretation include referencing the interpretations of main figures of reformist movements, fidelity to the school of thought tradition, criticism of teachings and practices of Sufism contradicting the Qur’an and Sunnah by citing the opinions of Ibn Taymiyyah, acceptance of weak (da'if ) hadiths, and having mythological dimensions.